2017
DOI: 10.1016/j.jadohealth.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Youth's Daily Activities and Situational Triggers of Gunshot Assault in Urban Environments

Abstract: Purpose Although previous research has made progress in identifying individuals predicted to face an elevated risk of being shot, it is not clear how that risk varies within individuals based on the contexts they encounter as they navigate daily life. The current study examines how the convergence of individual risk activity and neighborhood disadvantage and disorder triggers the risk of being shot. Methods Using a novel geographic information system (GIS) application, 123 male gunshot assault victims betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Research that extends beyond individual-level factors to include risk assessment across multiple ecological levels, with a focus on the intersection between family, peer, and communitylevel factors, is also needed. Most research beyond the individual level has focused on peers and families, 22,23 with community factors lacking. 22,23 The few community studies that have addressed more macro-level issues such as neighborhood socioeconomic variables have not focused on social relationships (eg, social capital and neighborhood monitoring).…”
Section: Epidemiology and Risk And Protective Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research that extends beyond individual-level factors to include risk assessment across multiple ecological levels, with a focus on the intersection between family, peer, and communitylevel factors, is also needed. Most research beyond the individual level has focused on peers and families, 22,23 with community factors lacking. 22,23 The few community studies that have addressed more macro-level issues such as neighborhood socioeconomic variables have not focused on social relationships (eg, social capital and neighborhood monitoring).…”
Section: Epidemiology and Risk And Protective Factorsmentioning
confidence: 99%
“…Most research beyond the individual level has focused on peers and families, 22,23 with community factors lacking. 22,23 The few community studies that have addressed more macro-level issues such as neighborhood socioeconomic variables have not focused on social relationships (eg, social capital and neighborhood monitoring). Only 2 studies have examined the intersection of peer relationships with community macrolevel variables.…”
Section: Epidemiology and Risk And Protective Factorsmentioning
confidence: 99%
“…However, other factors such as COVID-19-induced economic crisis and subsequently increased neighborhood violence/crime rates may have played a more significant role in elevating pediatric firearm assaults/homicides. The elevated rates of pediatric firearm assaults/homicides is likely the result of a combination of increased intentional assaults as well as increased frequency of innocent children injured as bystanders amidst adult crime [ 13 , [26] , [27] , [28] , [29] ]. The current ICD coding system does not clearly convey the intended target of a firearm assault, and some have called for revisions to the current ICD coding system for this reason [30] .…”
Section: Discussionmentioning
confidence: 99%
“…As one example, our measures of guardianship relied heavily on parental monitoring, but most of the victimization incidences occurred outside the home and, possibly, outside the neighborhood. Much prior research has indicated that capable guardians out in the community (Dong et al, 2017;Reynald, 2009Reynald, , 2010 can moderate individual risk even in highrisk environments. If we had more specific measures of guardianship (and guardianship intensity) in the community, we might have found the protective effect of guardianship against victimization that has been seen in previous literature.…”
Section: Discussionmentioning
confidence: 99%